MENCARI OPTIMASI INJEKSI SURFAKTAN-POLIMER MELALUI ANALISA SENSITIVITAS PARAMETRIK MENGGUNAKAN SIMULATOR - Iqbal, Muhamad
Enhanced Oil Recovery (EOR) technique is one of effective method in order to maximize oil recovery from a reservoir. One of the most common EOR method is by using chemical injection, such as surfactant and polymer flooding. Surfactant can improve oil recovery by reducing oil-water interfacial tension (IFT), while polymer can increase the viscosity of injected water thus improving the ability of water in sweeping oil. Nowadays, industry even use the combination of surfactant and polymer injection, which is known as surfactant-polymer (SP) flooding, in order to obtain better results. In field implementation, it’s necessary to have accurate injection designs in order to optimize the oil recovery. This thesis will discuss the sensitivity studies of several chemical injection parameters to the recovery factor value by using reservoir simulation method. The sensitivity of injection parameters that will be analyzed are injection timing, injection rate, chemical concentration, and total injection volume. Based on the sensitivity tests, it is known that polymer injection will cause a significant increase of oil production gradient profile in the early injection period, and the gradient tend to drop drastically after breakthrough happened. On the other side, surfactant injection will not cause very significant increase on the oil production gradient, but tend to be more stable than polymer usage. It is also known that the most affecting factor in incremental oil recovery of surfactant and polymer flooding are range and rate of injection, with recovery factor interval consecutively 7.576% and 2.431%. In SP flooding method, it has been found out that the increases of either surfactant or polymer will reduce the recovery factor, while the concentration of polymer tend to have more dominant effect than surfactant does. From all the tested case, it also known that SP flooding method gives higher recovery factor improvement on MS field than the usage of only one chemical substance, with the value of 12.767%.